2010
DOI: 10.3325/cmj.2010.51.23
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of 8 Genetic Loci for Serum Uric Acid Concentration

Abstract: AimTo investigate the value of genomic information in prediction of individual serum uric acid concentrations.Methods Three population samples were investigated: from isolated Adriatic island communities of Vis (n = 980) and Korčula (n = 944), and from general population of the city of Split (n = 507). Serum uric acid concentration was correlated with the genetic risk score based on 8 previously described genes: PDZK1, GCKR, SLC2A9, ABCG2, LR-RC16A, SLC17A1, SLC16A9, and SLC22A12, represented by a total of 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Recent genome-wide association studies (GWASs) identified multiple genetic loci associated with serum uric acid concentrations [ 9 , 13 , 18 , 26 , 27 ]. Our previous GWAS also confirmed two reported loci SLC2A9 (solute carrier family 2, facilitated glucose transporter member 9, 4p16.1) [ 18 , 22 , 26 , 28 , 29 ] and ABCG2 (ATP-binding cassette, sub-family G, member 2, 4q22) [ 12 , 30 , 31 ] positively associated with serum uric acid levels in a Chinese population [ 32 ]. Several studies investigated the associations between the genetic variants in the uric acid related loci of SLC2A9 and ABCG2 and the risk of CHD among Europeans [ 12 , 22 , 25 , 33 , 34 ] and found no association between them.…”
Section: Introductionsupporting
confidence: 84%
“…Recent genome-wide association studies (GWASs) identified multiple genetic loci associated with serum uric acid concentrations [ 9 , 13 , 18 , 26 , 27 ]. Our previous GWAS also confirmed two reported loci SLC2A9 (solute carrier family 2, facilitated glucose transporter member 9, 4p16.1) [ 18 , 22 , 26 , 28 , 29 ] and ABCG2 (ATP-binding cassette, sub-family G, member 2, 4q22) [ 12 , 30 , 31 ] positively associated with serum uric acid levels in a Chinese population [ 32 ]. Several studies investigated the associations between the genetic variants in the uric acid related loci of SLC2A9 and ABCG2 and the risk of CHD among Europeans [ 12 , 22 , 25 , 33 , 34 ] and found no association between them.…”
Section: Introductionsupporting
confidence: 84%
“…In type 2 diabetes, a disease commonly associated with gout, the C statistics of the prediction models using genetic information alone have been reported to range from 0.54 to 0.63 20,27,28,29 . The genetic aspects of uric acid have been indicated to be a good example of the polygenic trait theory 33 , and all of the genetic variants in this study have been shown to be associated with SUA level. Minimal effects of genetic variants for prediction have also been reported for obesity and premature coronary disease 30,31 .…”
Section: Rheumatologymentioning
confidence: 69%
“…Similarly, the GRS based in 8 loci located in almost the same genes than those in our study was also shown to correlate with serum UA levels in a recent meta-analysis of GWAS, 10 as well as in a Croatian population in a different study. 11 Our results, interpreted in the framework of Mendelian Randomization (MR), support the existence of a real connection between serum UA and PD risk, reasonably ruling out the possibility of confounding and reverse causation. Indeed, according to the MR approach, when a causal association exists between risk factor (UA) and disease endpoint (PD), the genetic variant that governs that risk factor should have a commensurate association with the disease itself.…”
Section: Discussionmentioning
confidence: 79%
“…Both sexes, analyzed separately, showed a significant inverse correlation between GRS and serum UA levels in men (r 2 5 20.18, P 5 .03; adjusted by age, P 5 .03), and these data were less significant in women (r 2 5 20.17, P 5 .06; adjusted by age, P 5 .08). The correlation The GRS represents the number of risk alleles related to low serum uric acid levels, divided into first tertile (2-7), second tertile (8)(9), and third tertile (10)(11)(12)(13)(14)(15). Maximum GRS after exclusion of SLC22A11 was 16.…”
Section: Resultsmentioning
confidence: 99%